The effect of non-cognitive traits on health behaviours in adolescence - Silvia Mendolia; Ian Walker (Institute for the Study of Labor (IZA), 2013)
This paper investigates the relationship between personality traits in adolescence and health behaviours using a large and recent cohort study. In particular, we investigate the impact of locus of control, self-esteem and conscientiousness at age 15-16, on the incidence of health behaviours such as: alcohol consumption; cannabis and other drug use; unprotected and early sexual activity; and sports and physical activity. We use matching methods to control for a very rich set of adolescent and family characteristics and we find that personality traits do affect health behaviours. In particular, individuals with external locus of control, or with low self-esteem, or with low levels of conscientiousness are more likely to engage in health-risky behaviours.
Keywords: I18; I28; 330; personality; locus of control; self-esteem; health behaviours